1996
DOI: 10.1021/bi961764n
|View full text |Cite
|
Sign up to set email alerts
|

Ras-Dependent Activation of Fibroblast Mitogen-Activated Protein Kinase by 5-HT1A Receptor via a G Protein βγ-Subunit-Initiated Pathway

Abstract: Serotonin (5-HT) is a potent mitogen in many cells types, an action which is frequently mediated through pertussis toxin-sensitive G proteins. In the current study, we used pharmacological inhibitors and dominant negative signaling constructs to delineate elements which participate in the activation of MAPK, a growth-associated mitogen-activated protein kinase, by human G protein-coupled 5-HT1A receptor transfected into CHO-K1 cells in a stable manner. The activation pathway does not directly involve phorbol e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 47 publications
6
111
1
Order By: Relevance
“…The relatively selective nature of the coupling of this receptor to G proteins would reduce potential ambiguities that might result from a more complex pattern of G protein coupling. This receptor has also been shown to stimulate both ERK [28,29] and NHE activities [30], and in the main, those data are consistent with a mutual regulatory pathway for NHE and ERK. However, it has been noted that rapid activation of ERK, but not of NHE, is sensitive to sequestration of G protein βγ-subunits, suggesting that ERK might not always be a proximal regulator of NHE in CHO cells over a short-time frame [29,30].…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…The relatively selective nature of the coupling of this receptor to G proteins would reduce potential ambiguities that might result from a more complex pattern of G protein coupling. This receptor has also been shown to stimulate both ERK [28,29] and NHE activities [30], and in the main, those data are consistent with a mutual regulatory pathway for NHE and ERK. However, it has been noted that rapid activation of ERK, but not of NHE, is sensitive to sequestration of G protein βγ-subunits, suggesting that ERK might not always be a proximal regulator of NHE in CHO cells over a short-time frame [29,30].…”
Section: Introductionsupporting
confidence: 67%
“…This receptor has also been shown to stimulate both ERK [28,29] and NHE activities [30], and in the main, those data are consistent with a mutual regulatory pathway for NHE and ERK. However, it has been noted that rapid activation of ERK, but not of NHE, is sensitive to sequestration of G protein βγ-subunits, suggesting that ERK might not always be a proximal regulator of NHE in CHO cells over a short-time frame [29,30]. Thus, the current studies were undertaken to establish whether ERK, when activated by the 5-HT "A receptor, is a rapid upstream regulator of NHE in CHO fibroblast cells.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…EMALA et al [94], confirming the observations of others [75,82], recently showed in human cultured airway smooth muscle cells that activation of Ras by ET was blocked by pertussis toxin, suggesting that the receptors for ET, which activate Ras, couple Gi but not Gq. Furthermore, in the same study, overexpression of a G protein bc-subunit scavenger failed to prevent activation of Ras, indicating that ET receptors most probably couple to a Gi that activates Ras via the Gia subunit [94] and not a Gibc (or Gqbc) subunit as proposed in other cell types [92,95] (fig. 3).…”
Section: Extracellular Signal-regulated Kinase Activation By G Proteimentioning
confidence: 70%